Nursing practice in care of patients with bedsores - Lazauskaitė, Vaida; Urbonienė, Asta (Slauga. Mokslas ir praktika, 2020)
The article analyzes activities of a nurse, caring for patients with bedsores. The topic is relevant for an aging society as bedsores are becoming one of the most common health problems. Bedsores cause not only health, but also a variety of quality of life related problems: decreased mobility, inability to self-sufficiency, social deprivation. Man becomes dependent on others, caring of him people. Only early prevention, proper wound care and careful patient‘s nursing can reduce healing time and improve quality of patient‘s life - this is what the article studies. The study involved twenty three X maintenance therapy and hospice nurses. Applied the questionnaire method.It was found that X maintenance therapy and hospice nurses point out the increment of wound purulent exudateas the most important indicator of wound infection, and the most frequently used bedsore prevention measures are rolling patients over every two hours, also appropriate hygiene. Other, less frequently mentioned preventive measures are: rollers, pads, antibedsore mattresses, physical therapy and medication. In care of patients with bedsores. X hospital nurses do not use the rubber wheel and spirit, they believe that it is even more traumatic for an existing wound.